Organizational Administration of Zone 5 Pariyatti Schools, General Education Division, Guided by the Threefold Training Principles - Gabhîro (Samerdee), Phra Yod; Chetiyanurak, Asst. Prof. Dr, Phrakhru Pariyatti; Kotsupho, Phisit (MCU Haripunchai Review, 2026)
This study aimed to 1) examine the administration of education at the Pariyatti Dhamma School, General Education Division, District 5, 2) analyze its administrative model, and 3) propose an administrative model based on the Threefold Training. This qualitative research targeted 28 participants, including 8 school administrators, 7 Dhamma teachers, 5 religious scholars, 5 officers from the Office of Pariyatti Education, and 3 student monks. Data were collected through interviews, document analysis, and descriptive analysis. The research results found that 1) The administration at the Pariyatti Dhamma School, General Education Division, District 5, focuses on holistic development, integrating both secular and spiritual education. Administration involves managing resources—human, material, and financial—in alignment with curriculum objectives. The school aims to cultivate monks and novices with morality, knowledge, and adherence to the Dhamma-Vinaya. Since its establishment in 1971, administrators, teachers, and staff have continuously implemented educational activities to enhance quality and develop desired learner attributes. 2) The school employs an integrated administrative model covering four main areas: self-management, personnel management, operational management, and strategic planning. This model supports the development of religious successors with both secular and Dhamma knowledge, as well as moral and ethical values. The administration has been found highly suitable and serves as a potential model for Thai monastic education. 3) The proposed administrative model based on the Threefold Training: Sīla–Samādhi–Paṇñā) consists of three dimensions: Sīla (discipline) for establishing organizational rules, ethical standards, and responsibility; Citta (mind) for fostering concentration, determination, and teamwork; and Paññā (wisdom) for enhancing knowledge, skills, and innovation. This model applies to the four areas of administration and uses the Threefold Training as the central framework to create a learning organization imbued with morality, concentration, and wisdom, supporting sustainable development of the Pariyatti Dhamma School.